2021
DOI: 10.1002/ajmg.a.62050
|View full text |Cite
|
Sign up to set email alerts
|

Adult diagnosis of Townes–Brocks syndrome with renal failure: Two related cases and review of literature

Abstract: Townes–Brocks syndrome (TBS) is a rare autosomal dominant syndrome, resulting from heterozygous variant in SALL1 gene and initially characterized by the triad of anorectal, thumb, and ear malformations. Essentially described in children, adult case reports are uncommon. Renal involvement has already been reported in adults and children but poorly described. Structural abnormalities such as hypodysplasia, unilateral renal agenesis or multicystic kidneys have been described, as well as functional impairment (wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
1
10
0
1
Order By: Relevance
“…28% of the patients had serum creatinine levels above the normal range but did not meet the diagnosis of renal failure, hence, were considered having renal injury. Five patients underwent successful kidney transplants and two of them developed graft rejection [ 11 14 ]. The patients were grouped based on the location of the SALL1 mutations they carried (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…28% of the patients had serum creatinine levels above the normal range but did not meet the diagnosis of renal failure, hence, were considered having renal injury. Five patients underwent successful kidney transplants and two of them developed graft rejection [ 11 14 ]. The patients were grouped based on the location of the SALL1 mutations they carried (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that renal anomalies, including functional impairment with or without structural abnormalities, were detected in 43% of patients with TBS. Recently, Beaudoux et al [ 3 ] reported two related TBS cases that exhibited kidney hypoplasia (focal and segmental glomerulosclerosis) and ESRD. Their literature review showed that 10 of 44 adult cases of TBS with genetic confirmation had kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is an autosomal dominant syndrome caused by a pathogenic variant of SALL1 gene[ 1 ]. This syndrome was first described by Townes and Brocks in 1972, and the mutations in SALL1 responsible for TBS were first identified by Kohlhase in 1998[ 2 , 3 ]. Thereafter, many TBS cases were found with pathogenic variants of SALL1 to make a molecular diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Almost half of the individuals had varying degrees of renal impairment, and 22% of the individuals progressed to renal failure. Some of the patients successfully underwent kidney transplantation, and two of them experienced graft rejection[ 3 , 7 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%